2016
DOI: 10.1016/j.bbmt.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Haploidentical Natural Killer Cells Infused before Allogeneic Stem Cell Transplantation for Myeloid Malignancies: A Phase I Trial

Abstract: Allogeneic stem cell transplantation is an effective treatment for high-risk myeloid malignancies, but relapse remains the major post-transplant cause of treatment failure. Alloreactive NK cells mediate a potent antileukemic effect and may also enhance engraftment and reduce GvHD. Haploidentical transplants provide a setting in which NK cell alloreactivity can be manipulated, but are associated with high rates of GvHD. We performed a phase I study infusing escalating doses of NK cells from an HLA haploidentica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(93 citation statements)
references
References 35 publications
3
90
0
Order By: Relevance
“…14 Recently, increasing evidence from preclinical and clinical studies supports the potential efficacy of NK cell therapeutics in multiple cancer types. 15-19 Clinical studies also showed a positive correlation between outcomes of the therapy and the dose of NK cells administered, prompting the development of effective methods to grow NK cell in vitro . 19,20 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Recently, increasing evidence from preclinical and clinical studies supports the potential efficacy of NK cell therapeutics in multiple cancer types. 15-19 Clinical studies also showed a positive correlation between outcomes of the therapy and the dose of NK cells administered, prompting the development of effective methods to grow NK cell in vitro . 19,20 …”
Section: Introductionmentioning
confidence: 99%
“…15-19 Clinical studies also showed a positive correlation between outcomes of the therapy and the dose of NK cells administered, prompting the development of effective methods to grow NK cell in vitro . 19,20 …”
Section: Introductionmentioning
confidence: 99%
“…Autologous mononuclear cells incubated with IL‐2 and CD3 to produce cytokine‐induced killer (CIK) cells have shown promising results as an adjuvant therapy for HCC, with improved recurrence‐free survival . Allogeniec and haploidentical NK cell infusions have aimed to capitalise on KIR‐HLA mismatch, resulting in a loss of inhibition of infused NK cells coupled with tumour‐induced activation because of an increase in surface expression of stress‐induced ligands on tumour cells . Although no major detrimental side effects have been cited for these infusions, direct anti‐tumour efficacy has not yet been proven in solid tumours, and issues remain with determining the longevity of infused NK cell responses.…”
Section: Therapeutic Prospects: Nk Cell Expansion and Adoptive Transfmentioning
confidence: 99%
“…NK cell-based therapy has been utilized in the setting of an allotransplant to enhance the GVL effect without compromising graft integrity (117,118). Advances in cellular processing and increased access to good manufacturing practices-compliant (GMP-compliant) laboratories has enabled ex vivo activation and expansion (using IL-2 or IL-15) of donor-derived NK cells for use in patients with active disease (119).…”
Section: Adoptive Cellular Therapymentioning
confidence: 99%